2020
DOI: 10.1021/acsomega.9b03216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Formulation of Four-Arm PolyDMAEA-siRNA Polyplex for Transient Downregulation of Collagen Type III Gene Expression in TGF-β1 Stimulated Tenocyte Culture

Abstract: The natural healing process for tendon repair is associated with high upregulation of collagen type III, leading to scar tissue and tendon adhesions with functionally deficient tendons. Gene delivery systems are widely reported as potential nanotherapeutics to treat diseases, providing a promising approach to modulate collagen type III synthesis. This work investigates a proof-of-concept four-arm cationic polymer-siRNA polyplex to mediate a transient downregulation of collagen type III expression in a tendon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Gene expression in tendon cells has been shown to change with culture (Shukunami et al, 2018; Yao, Bestwick, Bestwick, Maffulli, & Aspden, 2006) and can change rapidly from the expression levels found in the native tissue (Kuemmerle et al, 2016). However, we have previously demonstrated that COL3A1 gene expression levels do not change between passages 0 and 10 during equine tenocyte culture (Liao et al, 2020). Additionally, although there is a significantly higher level of COL1A1 in equine tenocytes at passage 0 than at passage 3, there are no further changes in COL1A1 expression beyond passage 3 (Liao et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Gene expression in tendon cells has been shown to change with culture (Shukunami et al, 2018; Yao, Bestwick, Bestwick, Maffulli, & Aspden, 2006) and can change rapidly from the expression levels found in the native tissue (Kuemmerle et al, 2016). However, we have previously demonstrated that COL3A1 gene expression levels do not change between passages 0 and 10 during equine tenocyte culture (Liao et al, 2020). Additionally, although there is a significantly higher level of COL1A1 in equine tenocytes at passage 0 than at passage 3, there are no further changes in COL1A1 expression beyond passage 3 (Liao et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…However, we have previously demonstrated that COL3A1 gene expression levels do not change between passages 0 and 10 during equine tenocyte culture (Liao et al, 2020). Additionally, although there is a significantly higher level of COL1A1 in equine tenocytes at passage 0 than at passage 3, there are no further changes in COL1A1 expression beyond passage 3 (Liao et al, 2020). Furthermore, there is no significant difference in collagen gel contraction and response to inflammation in equine tenocytes used between passages 4 and 11 (McClellan, Evans, et al, 2019).…”
Section: Discussionmentioning
confidence: 89%
“…Previous reports studying the charge reversal of pDMAEA into pAA have identified a pH-independent self-catalyzed hydrolysis mechanism. However, most of these studies utilize block copolymers, homopolymers, ,,, or statistical copolymers containing co-monomers with complementary functionalities such that there is limited spacing between basic residues within the chain . Given this, we were interested in identifying if the relative lipophilicity of the copolymers impacted the rate of pDMAEA hydrolysis and its pH-independent mechanism.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Notable examples include enhanced mRNA delivery utilizing an oligo­(carbonate-β–α-amino ester), which rapidly degrades into a neutral diketopiperazine through an ester–amide cyclization reaction, releasing the mRNA . Another key example is the self-catalyzed hydrolysis of poly­(dimethylaminoethyl) acrylate (pDMAEA), which degrades from a polycation into polyanionic poly­(acrylic acid) (pAA) in the presence of water releasing dimethylaminoethanol (DMAE). From a gene delivery perspective, this delivery system will efficiently condense nucleic acids in their positively charged state and then hydrolyze, charge invert, repell, and release the genetic cargo using a single material. Systems based on the charge-reversing nature of pDMAEA have already been utilized to deliver siRNA ,, and pDNA; however, no studies have yet examined its potential for mRNA delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation